Transformasi Digital Lembaga Keuangan Syariah: Strategi Inklusi dan Literasi Keuangan - Husni Shabri; Khairulis Shobirin; Nita Fitria; Rahmi Pamel (MABIS Jurnal Manajemen Bisnis Syariah, 2026)
This study examines the role of digital transformation in improving Islamic financial inclusion and Islamic financial literacy in Indonesia, with Islamic financial inclusion acting as a mediating variable. The study addresses a research gap in previous studies that mostly examined digitalization and Islamic financial literacy separately without comprehensively analyzing the mediating mechanism of Islamic financial inclusion. A quantitative explanatory approach was employed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) on data collected from 150 users of Islamic digital financial services. The findings demonstrate that digital transformation significantly enhances Islamic financial inclusion and Islamic financial literacy. Islamic financial inclusion also significantly improves Islamic financial literacy and partially mediates the relationship between digital transformation and financial literacy. These findings indicate that digital services such as Islamic mobile banking, QRIS, and Islamic fintech not only broaden financial access but also strengthen public understanding of Islamic financial products and principles. This study contributes theoretically by integrating digital transformation, Islamic financial inclusion, and financial literacy into a single empirical model, while practically providing recommendations for Islamic financial institutions to strengthen digital-based financial education and inclusion strategies